Older Adults' Access to and Satisfaction With Primary Hospitals Based on Spatial and Non-spatial Analyses - Yu, Jingyu; Leung, Mei-yung; Ma, Guixia; Xia, Jingcheng (Frontiers in Public Health, 2022)
In order to improve the health and quality of life of older adults, the Chinese government is dedicated to establishing an equilibrium level of primary healthcare services for all communities. However, little attention has been paid to measuring the accessibility of primary hospitals to older adults, nor to understanding the seniors’ satisfaction with and needs for primary healthcare services. Therefore, this study sought to investigate the spatial accessibility of primary hospitals to older adults, and also to examine the impact of walking distances on the seniors’ satisfaction with their healthcare services. A two-step floating catchment area method was applied to measure the spatial accessibility of primary hospitals to older adults at the level of subdistricts. In order to investigate the actual opinions of older adults and verify the results of spatial analysis, a large-scale questionnaire survey was also conducted. The analyses found that (1) primary hospitals were not equally distributed; (2) most older adults did not have access to primary hospitals within a threshold walking distance of 1,000 m, but they usually could reach a hospital in their subdistrict within a threshold distance of 2,000 m; (3) older adults’ satisfaction levels with primary hospitals were significantly different among subdistricts; (4) long walking distances negatively influenced older adults’ satisfaction with primary hospitals; (5) the satisfaction of older adults was highest with a threshold distance of 500 m; and (6) a piecewise regression model indicated that older adults’ satisfaction with primary hospitals would decrease with an increase in walking distance to the hospital. When the walking distances exceeded 1,000 m, the slope of the linear regression model increased significantly compared with the slope for walking distances less than 1,000 m. By adopting multiple research methods and capturing older adults’ behaviors and satisfaction, our results provide (1) data on the importance of accessibility of primary hospitals to older adults, and (2) insights for future planning to achieve equity in primary healthcare and enhance the spatial distribution of primary hospitals.